Z Mawardi Effendi: Perjalanan Karir Seorang Akademisi dan Mantan Rektor Universitas Negeri Padang Dua Periode (1975-2020) - Vera Yuliana; Etmi Hardi (Jurusan Sejarah FIS UNP, 2021)
This research aims to provide an overview of the life and career journey of Z Mawardi Effendi and his role in leading the State University of Padang as rector of two periods. Therefore, the first stage is to collect data from oral and written sources. The second stage is the criticism of sources both internal and external sources. Next, the third stage is the analysis and interpretation of data. Lastly, the fourth stage is to describe the results of research in the form of scientific writing in accordance with the rules of historical research. The conclusion of this study is that Z Mawardi Effendi is an academic figure from Koto Panjang, Tanah Datar and has a career at Padang State University for approximately 50 years. He started his career as a young lecturer in 1975 and briefly served several administrative roles continuously ranging from Head of Learning Resources Center, Vice Dean, Dean, Vice Rector, to the highest administrative position in a university, namely Rector. Not only that, after serving as Rector, he also held other positions such as Chairman of Postgraduate Program and Chairman of The Senate of Padang State University. The position continued until the end of retirement so that it has many roles for the State University of Padang. Keywords: Biography, Figure, Education, Lecturer, Rector